Supplier development framework in the Malaysian automotive industry: Proton’s experience - Abdullah, Rashid; Lall, Maharjan Keshav; Tatsuo, Kimbara (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
In a dynamic market, firms need to evolve from traditional to strategic purchasing which aims to reduce the cost of the purchase and that might imply standardization of components, delivery time and levels of inventory. This effort will usually include key suppliers as joint problem solvers and with these problem-solving models to work with; the firm’s attitude towards suppliers may change from confrontation to trust and partnership. From the buyer-supplier relationship perspective, the procurement practice of the buyer is critical and acts as a window to nurture the supplier development effort. This article presents the result of a study on supplier development in the Malaysian automotive industry, which focused on PROTON, and its role in developing the suppliers’ relationships and development. This study indicates that PROTON and its suppliers’ development program plays a crucial role in developing and extending comprehensive support to its supplier’s firm such as supplier selection and appointment, development, match making, and promoting continuous performance development and improvement programs.